Does environmental regulation truly enhance corporate green environmental investment? Evidence from the supervision of independent directors in listed companies - Wang, Chao; Wang, Feifei; Jiang, Ping (Frontiers in Psychology, 2024)
With the increasingly prominent environmental issues in China, the government and citizens alike have intensified their focus on corporate investments in green environmental protection. Nevertheless, as government regulations become more stringent, there is substantial debate over whether environmental regulatory policies can consistently encourage listed companies to increase green environmental investments. Simultaneously, independent board supervision plays a crucial role in promoting the compliance and sustainability of listed companies regarding environmental protection. This paper selected a sample of 246 Chinese listed companies from 2010 to 2019, and used a fixed effects model to examine the impact of environmental regulation on the environmental investment of listed companies in China. Moreover, we used a mediation effect model to analyze the role of independent director supervision in influencing the relationship between environmental regulation and companies’ green environmental investment. Additionally, we discuss the heterogeneous impact of environmental regulations on corporate environmental investments. Our findings are as follows: first, during the sample period, the tightening of environmental regulations significantly reduces the growth of environmental investment among the studied firms. As government environmental regulatory policies gradually intensify, the negative impact on environmental investments by listed companies becomes increasingly evident. Second, independent directors help alleviate the adverse impacts of environmental regulations on the environmental investment levels of listed companies. This suggests that the inclusion of independent directors in board governance plays a role in assessing government environmental regulatory policies and overseeing corporate decisions related to environmental investment. Lastly, the heterogeneity analysis indicates that environmental regulation significantly negatively impacts the environmental investment of listed companies in pollution-intensive industries and those located in the western regions. Furthermore, environmental regulatory policies impose greater constraints on the environmental investments of small-sized listed companies compared to their large-sized counterparts.